Immigrating into a recession: Evidence from family migrants to the U.S. - Toman Barsbai; Andreas Steinmayr; Christoph Winter (Kiel Institute for the World Economy (IfW Kiel), 2023)
We analyze the impact of economic conditions at arrival on the economic integration of family-sponsored migrants in the U.S. A one pp higher unemployment rate at arrival decreases annual wage income by four percent in the short run and two percent in the longer run. The loss in wage income results primarily from lower hourly wages due to occupational downgrading. Migrant and family networks help mitigating the negative labor market effects. Migrants who arrive during a recession take up occupations with higher concentrations of fellow countrypeople and are more likely to reside with family members, potentially reducing their geographical mobility.
Keywords: E32; F22; J31; J61; 330; Immigrant integration; family reunification; chain migration; migrant networks; labor market; business cycle